[Rezension von: Buckley, Jorunn Jacobsen, 1800 years of encounters with Mandaeans] - Häberl, Charles G. (JAOS, 2025)
1800 Years of Encounters with Mandaeans. By Jorunn J . Buckley. Gorgias Mandaean Series, vol. 5. Gorgias Press, 2023. Pp. xxxiv + 112. $114.95.